A qualitative examination of substance use service needs among people who use drugs (PWUD) with treatment and service experience in Ontario, Canada - Cayley Russell; Farihah Ali; Frishta Nafeh; Sean LeBlanc; Sameer Imtiaz; Tara Elton-Marshall; Jürgen Rehm (BMC, 2021)
Abstract Background People who use drugs (PWUD) often have complex health and social support needs related to substance use, yet face numerous barriers to service access, resulting in unmet treatment needs and a corresponding gap in treatment. While initiatives to scale up substance use services for PWUD in Canada - and Ontario - have been undertaken, these have excluded PWUD' perspectives, and their needs have largely been defined by other actors. As end-users of services, PWUD' perspectives are vital to understanding what services are required, and whether existent services are adequate, appropriate and effective. Thus, the present study aimed to elicit in-depth knowledge from PWUD with lived experience of accessing services to better understand their unmet treatment and service needs, towards closing the service and treatment gap in Ontario. Methods This qualitative study included one-on-one interviews conducted with a cohort of n = 45 adult PWUD with substance use and treatment experience in Ontario, Canada. Participants were recruited from substance use services based on ConnexOntario's directory of all provincial addiction services, as well as by word-of-mouth. Questions focused on participants' experiences and perspectives on substance use services towards understanding their service needs. Data underwent an inductive thematic analysis based on key themes that emerged. Results Participants commonly engaged in polysubstance use, and identified a number of unmet substance use service needs including complex factors within the current service system that influenced access to available programs. Specifically, participants suggested the need to address stigmatization and system fragmentation, increase service provision and capacity, and scale up specific services and related supports such as harm reduction, counseling, treatment, and housing. Conclusions This study identified PWUD' needs in relation to substance use service provision in Ontario, Canada, and highlighted important areas for policy change and program planning and implementation. Concrete recommendations include the development of a government-funded, low-barrier, comprehensive and integrated service delivery and referral models that include PWUD as collaborators and program facilitators to ensure that services are as accessible, effective, and cohesive as possible. Results from this study can be used to enhance provincial substance use treatment and service provision.